Complete Growth Inhibition of Pseudomonas aeruginosa by Organo-Selenium-Incorporated Urinary Catheter Material - Phat L. Tran; Caroline L. Presson; Md Nayeem Hasan Kashem; Wei Li; Ted W. Reid; Werner T. W. de Riese (MDPI AG, 2024)
To further investigate the inhibition of Pseudomonas aeruginosa's in vitro growth and biofilm formation by an organo-selenium-incorporated polyurethane (PU) catheter material. P. aeruginosa, Staphylococcus aureus, and Candida albicans were incubated in vitro with organo-selenium and control polyurethane catheter materials in the presence of glutathione. Growth was evaluated by a colony-forming-unit (CFU) count and visualized with confocal laser scanning microscopy. Two different PU catheter materials were used. Using tin-catalyzed PU catheter material, complete inhibition of S. aureus was seen at 1% selenium (Se), whereas no inhibition was seen for P. aeruginosa at up to 3.0% Se. Whereas, using a thermoplastic PU catheter material, 1.5% Se and 2% Se organo-selenium caused several logs of growth inhibition of P. aeruginosa, and 2.5% selenium, incorporation showed complete inhibition (8 logs). Samples with lower than 1.5% selenium did not show adequate growth inhibition for P. aeruginosa. Similar in vitro growth inhibition was achieved against a multidrug-resistant C. albicans strain. It was concluded that optimal inhibition of P. aeruginosa in vitro growth and biofilm formation occurs with 2.5% selenium incorporated as organo-selenium in a thermoplastic PU catheter material. These results suggest that reduced incidence of CAUTIs (catheter associated urinary tract infections) with P. aeruginosa and other bacteria and fungi can be achieved by using organo-selenium-incorporated catheters.